2014
DOI: 10.1111/nph.13153
|View full text |Cite
|
Sign up to set email alerts
|

Replicate altitudinal clines reveal that evolutionary flexibility underlies adaptation to drought stress in annual Mimulus guttatus

Abstract: SummaryExamining how morphology, life history and physiology vary along environmental clines can reveal functional insight into adaptations to climate and thus inform predictions about evolutionary responses to global change. Widespread species occurring over latitudinal and altitudinal gradients in seasonal water availability are excellent systems for investigating multivariate adaptation to drought stress.Under common garden conditions, we characterized variation in 27 traits for 52 annual populations of Mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
203
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(217 citation statements)
references
References 76 publications
9
203
2
3
Order By: Relevance
“…For example, clinal patterns of phenotypic differentiation have very recently been characterized in monkeyflowers [123], Ivyleaf morning glories [124], Sakhalin firs [125], Anolis lizards [126], and Japanese sika deer [127]. Connecting these recent examples of phenotypic variation to patterns of genomic variation will clearly be a fruitful avenue for future exploration.…”
Section: The Future Of Clinal Genomicsmentioning
confidence: 99%
“…For example, clinal patterns of phenotypic differentiation have very recently been characterized in monkeyflowers [123], Ivyleaf morning glories [124], Sakhalin firs [125], Anolis lizards [126], and Japanese sika deer [127]. Connecting these recent examples of phenotypic variation to patterns of genomic variation will clearly be a fruitful avenue for future exploration.…”
Section: The Future Of Clinal Genomicsmentioning
confidence: 99%
“…A comprehensive understanding of the molecular mechanisms that underlie drought responses is required for classical breeding or genetic modification of crop species for enhanced drought tolerance. To date, hundreds of genes have been identified that control key processes in the plant responses to drought stress, such as stress signal perception (Osakabe et al, 2013;Zhu, 2016), signal transduction and amplification (Kim, 2014), and adaptation (Kooyers et al, 2015). The potential of a number of these genes to improve the drought tolerance of crop species has been demonstrated in field trials (Hu and Xiong, 2014).…”
mentioning
confidence: 99%
“…Many plants (Arabidopsis, Phyllostachys heterocycla, Mimulus guttatus, etc.) accelerate flowering to complete life cycle under drought conditions (Peng et al, 2013;Wolfe and Tonsor, 2014;Kooyers et al, 2015), a phenomenon referred to as drought escape (DE). Because drought triggers phytohormone abscisic acid (ABA) biosynthesis and signal transduction, it has been proposed that ABA mediates DE response.…”
mentioning
confidence: 99%